Creativity and religion Hubungan Antara Kreativitas Dengan Hasil Belajar Agama Islam di SMKN 5 Kabupaten Tangerang: Creativity, output study, islam religion - Syafa'at Ariful Huda (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
Analysis of Islamic religious learning outcomes in SMKN 5, Tangerang Regency. "This study aims to "analyze the relationship between creativity and Islamic learning outcomes."This research was conducted to students of SMKN 5 Tangerang Regency. The sample was taken by simple random sampling (sampling random sampling) by taking 30 students from 3 class XI, amounting to 90. "The research method used is a descriptive qualitative method with the technique" correlation. The independent variable (X) is creativity and the dependent variable "(Y) is the result of learning Islam. "The data obtained were analyzed first with the normality test using the lilliefors test, then the correlation coefficient test and the significance coefficient correlation test." = 0.40. Furthermore, calculating the significance of the coefficient with the t-student test obtained thit = 2.52 (ttab = 2.05) so that the conclusion is there is a relationship between creativity with the learning outcomes of Islamic religion.